Future projection of East China Sea temperature by dynamic downscaling of the IPCC AR4 CCSM3 model result - 于晓林 王凡 唐晓晖 (Chinese journal of oceanology and limnology, 2012)
Future temperature distributions of the marginal Chinese seas are studied by dynamic downscaling of global CCSM3 IPCC_AR4 scenario runs. Different forcing fields from 2080–2099 Special Report on Emissions Scenarios (SRES) B1, A1, and A2 to 1980–1999 20C3M are averaged and superimposed on CORE2 and SODA2.2.4 data to force high-resolution regional future simulations using the Regional Ocean Modeling System (ROMS). Volume transport increments in downscaling simulation support the CCSM3 result that with a weakening subtropical gyre circulation, the Kuroshio Current in the East China Sea (ECS) is possibly strengthened under the global warming scheme. This mostly relates to local wind change, whereby the summer monsoon is strengthened and winter monsoon weakened. Future temperature fluxes and their seasonal variations are larger than in the CCSM3 result. Downscaling 100 years’ temperature increments are comparable to the CCSM3, with a minimum in B1 scenario of 1.2–2.0°C and a maximum in A2 scenario of 2.5–4.5°C. More detailed temperature distributions are shown in the downscaling simulation. Larger increments are in the Bohai Sea and middle Yellow Sea, and smaller increments near the southeast coast of China, west coast of Korea, and southern ECS. There is a reduction of advective heat north of Taiwan Island and west of Tsushima in summer, and along the southern part of the Yellow Sea warm current in winter. There is enhancement of advective heat in the northern Yellow Sea in winter, related to the delicate temperature increment distribution. At 50 meter depth, the Yellow Sea cold water mass is destroyed. Our simulations suggest that in the formation season of the cold water mass, regional temperature is higher in the future and the water remains at the bottom until next summer. In summer, the mixed layer is deeper, making it much easier for the strengthened surface heat flux to penetrate to the bottom of this water.